2010
DOI: 10.1021/jp101033w
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study on Compound I Redox-Active Species in Horseradish Peroxydase Enzyme: Conformational Fluctuations and Solvation Effects

Abstract: Molecular dynamics simulations for the compound I species in horseradish peroxidase were carried out over a nanoseconds time-scale. Results indicate that the supramolecular assembly composed of compound I in interaction with highly conserved distal residues (His42 and Arg38) exists in two well-defined conformations basically differing in the local position of the distal histidine (i.e., His42). Furthermore, we observe the presence of a biological channel in the distal side of the heme cavity, between Arg38 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In particular, C c P Cpd I has a protein radical (on Trp 191 ), while HRP and APX have a heme-based radical. Extensive computational studies using density functional theory, quantum mechanics/molecular mechanics and molecular dynamics studies have been performed on the various stages of the catalytic cycle of peroxidases and particularly on Cpd I [ 44 , 45 , 46 , 47 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. These studies ( Scheme 1 ) confirmed Cpd I as a triradical species with three unpaired electrons, whereby two of those are on the metal (in the π* xz and π* yz orbitals), while the third radical is non-metal based [ 53 , 57 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, C c P Cpd I has a protein radical (on Trp 191 ), while HRP and APX have a heme-based radical. Extensive computational studies using density functional theory, quantum mechanics/molecular mechanics and molecular dynamics studies have been performed on the various stages of the catalytic cycle of peroxidases and particularly on Cpd I [ 44 , 45 , 46 , 47 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. These studies ( Scheme 1 ) confirmed Cpd I as a triradical species with three unpaired electrons, whereby two of those are on the metal (in the π* xz and π* yz orbitals), while the third radical is non-metal based [ 53 , 57 , 61 ].…”
Section: Introductionmentioning
confidence: 99%